THE EFFECT OF SALINITY ON GROWTH, ION ACCUMULATION AND YIELD OF RICE VARIETIES - M. A. Hakim; 2; A. S. Juraimi; M. M. Hanafi; M. R. Ismail; M. Y. Rafii; M. M. Islam; A. Selamat (Journal of Animal and Plant Sciences, 2014)
The experiment was conducted to assess the responses of salinity on the growth, nutrient accumulation and yield of rice genotypes. Five Malaysian genotypes (MR33, MR52, MR211, MR232 and MR219), two salt sensitive (BRRI dhan 29 and IR20) and one salt tolerant genotypes (Pokkali) were evaluated in four levels of salinity. Two factors complete randomized design (CRD) was used with four replications. Dry weight of root, shoot and yield significantly decreased with the increase of salinity levels, while MR232 and MR211 were less affected. Na+ ions accumulations increased in the root and shoot with the increase of salinity, while the lowest accumulation was in MR211. Na+/ K+ratio sharply increased in the root with increasing the salinity. Whereas, Ca++/Na+ and Mg++/Ca++ ratio showed decreasing trend with increasing salinity level. The maximum amount of nitrogen and phosphorous accumulation was observed in the shoot of MR211, while Na+ in BRRI dhan29, K+ in Pokkali. The highest accumulation of Na+ and K+ observed in the root of MR219. The maximum Ca++ and Mg++ were found in MR33 and MR211, respectively. Considering all, genotypes MR211 andMR232 were found to be relatively tolerant to salt than the other genotypes.
Keywords: Salinity; Rice; yield; mineral nutrients; Malaysia